Қырғыз Республикасындағы құқық негіздерін техникалық реттеу (Journal of actual problems of jurisprudence, 2019)
In the case of the successful implementation of reforms and the necessary technical regulations will not only created a new technical legislation of the Kyrgyz Republic, but also the formation of a certain system of relationships between producers, consumers and the state in ensuring the safety of products and production processes.